The Development and Validation of a Personal Agency Scale Based in the Community Capitals Framework - Abigail Borron; Kevan W. Lamm; Keith Atkins (Journal of International Agricultural and Extension Education, 2020)
Used in a variety of community contexts and needs, the Community Capitals Framework (CCF) is an analytical tool to holistically examine the complex and unique characteristics that exist at the local level. While CCF—which focuses on social, human, cultural, political, natural, financial, and built capitals—has been used to collect community information to identify and assess suitable programming efforts, a gap currently exists in the literature providing agricultural and extension educators with the tools necessary to examine CCF characteristics, both at the community and individual levels. Designed as a pilot study targeting six counties in [STATE], this research developed a personal agency scale that was based on the seven capitals and intended to measure individuals’ perceived ability within a community. Internal structure validity was established by analyzing the response distributions of the individual items, evaluating internal consistency, and conducting exploratory factor analyses of the hypothesized latent variables. These results indicate that such a scale has potential to serve as a baseline set of data when considering program design, implementation, and evaluation purposes
Keywords: community capitals; community development; personal agency; scale development